2004
DOI: 10.3390/md203147
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Untenospongin B, a Metabolite from the Marine Sponge Hippospongia communis collected from the Atlantic Coast of Morocco

Abstract: (-)-Untenospongin B isolated from the marine sponge Hippospongia communis has been tested for its antimicrobial activity against bacteria and human pathogenic fungi using agar disk method and was found to possess a broad and strong activity toward the test organisms. Its antifungal activity was further characterized by determination of the minimum inhibitory concentration (MIC) against five fungal species using broth microdilution method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 10 publications
(12 reference statements)
1
22
0
Order By: Relevance
“…However, the fungal burden counted in the present study was very low in most of the samples. It seems that fungi occur in sponges at very low frequency, probably due to the antifungal activities of sponges as previously reported [18,19]. It has been found that, (+) -curcuphenol possesses a broad antifungal spectrum [18].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…However, the fungal burden counted in the present study was very low in most of the samples. It seems that fungi occur in sponges at very low frequency, probably due to the antifungal activities of sponges as previously reported [18,19]. It has been found that, (+) -curcuphenol possesses a broad antifungal spectrum [18].…”
Section: Discussionsupporting
confidence: 55%
“…It has been found that, (+) -curcuphenol possesses a broad antifungal spectrum [18]. Moreover, Rifai et al [19] assessed the inhibitory effect of Untenospongin B, a metabolite from the marine sponge Hippospongia communis against five fungal species (Candida albicans, Aspergillus fumigatus, Aspergillus niger, Arthroderma simu and Trichophyton rubrum), and it was found to possess a broad and strong activity toward the test organisms. Sponge associated bacteria [20], and a possible adverse physico-chemical condition in the environment of sponge structures, may also influence the fungal populations [5].…”
Section: Discussionmentioning
confidence: 99%
“…Kossuga et al, reported a new antifungal agent polyketide, (2S,3R)-2-aminododecan-3-ol, isolated from the Brazilian ascidian Clavelina oblonga, which was very active against C. albicans (MIC = 0.7 ± 0.05 μg/ml). Although the mechanism of action of this compound remains undetermined its bioactivity was comparable to the clinically used antifungal agents nystatin (MIC = 1 -4 μg/ml) and ketoconazole (MIC =1 -4 μg/ml) (Rifai et al, 2004).…”
Section: Fig 6d Anthelminthic and Antibacterial Compoundsmentioning
confidence: 86%
“…1). Fasciculatin, previously isolated from Ircinia fasciculata, was reported to have a moderate cytotoxicity and inhibition of lymphocyte proliferation [12]. Preliminary work on Acanthellin and Axisonitrile, indicated their utility as antimalarial drugs [13].…”
Section: Introductionmentioning
confidence: 99%